Pengaruh Model Pembelajaran Berbasis Masalah Terhadap Kemampuan Berpikir Kritis Matematis Siswa Kelas VIII SMP - Br. Sirait, Dina Meilinda (Unika Santo Thomas Medan, 2019)
This study aims to: (1) To determine the effect of problem-based learning models on mathematics critical thinking skills of junior high school students; (2) To find out the attitudes of students towards the problem-based learning model. The population in this study were eighth grade students of Junior High School of 28 Medan. By random sampling selected class VIII-F as an experimental class as many as 40 students and class VIII-E as a control class as many as 40 students. The data used in this study are quantitative data andÂ qualitative data. Quantitative data are data obtained from tests of students' critical thinking skills and qualitative data, namely data obtained from student attitude questionnaires. Based on the analysis of research data, obtained the following results: (1) the results of regression analysis obtained the equation = 51.89 + 23.57X means that the problem-based learning model has a positive effect with an average value of 75.46 mathematical thinking skills of students . From the results of the correlation it was found that the influence of the problem-based learning model was strong enough with the results of the correlation coefficient of 0.568 and the coefficient of determination of 32.3% so it can be concluded that the problem-based learning model influences students' critical thinking skills. (2) Based on student attitudinal response results it can be concluded that the student response is very positive towards the problembased learning model with an average of â‰¥ 86.03.